Self-initiated expatriation and self-initiated expatriates, clarification of the research stream - Doherty, N.; Richardson, Julia; Thorn, K. (Emerald Group Publishing Ltd., 2013)
Purpose – This paper aims to move towards clarification of the self-initiated expatriate/expatriation construct with the aim of extending and deepening theory development in the field. Design/methodology/approach – Drawing on Suddaby’s think piece on construct clarity, this paper applies his proposed four elements; definitional clarity, scope conditions, relationships between constructs and coherence, in order to clarify the SIE construct. Findings – The discussion examines the “problem of definition” and its impact on SIE scholarship. The spatial, temporal and value-laden constraints that must be considered by SIE scholars are expounded, and the links between SIE research and career theory are developed. From this, potential research agendas are proposed. Research limitations/implications – This is a conceptual piece which, rather than giving precise research data, encourages further thinking in the field. Originality/value – Although the definitional difficulties of SIEs have been identified in previous literature, this is the first attempt to clarify the boundaries of SIE and its interconnectedness with other related constructs.